The ideological use and abuse of Freiburg's ordoliberalism - Malte Dold; Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2019)
In the aftermath of the Eurozone crisis, a "battle of ideas" emerged over whether ordoliberalism is part of the cause or the solution of economic problems in Europe. While German ordoliberals argued that their policy proposals were largely ignored before and during the crisis, implying a too small role of ordoliberalism in European economic policy, critics saw too much ordoliberal influence, especially in form of austerity policies. We argue that neither view is entirely correct. Instead, both camps followed their ideological predispositions and argued strongly in favor of their preconceived Weltanschauung. The ordoliberal Freiburg School ceased being an active research program and instead grew to resemble a "tradition" whose proponents shared a certain mindset of convenience. As a result, ordoliberal thinking was both used and abused by its proponents and critics to emphasize their ideologically framed policy recommendations. The present paper analyzes this ongoing debate and reflects on how the different ideological camps refer to the Freiburg School to push their own agendas. Building on this discussion, we end our paper with some constructive thoughts on how a contemporary ordoliberalism might want to react to some of the challenges of the ongoing Eurozone crisis.
Keywords: B29; D43; E61; G18; P16; 330; Freiburg School; Ordoliberalism; Eurozone Crisis; Austerity; Ideology